(3GaYdgG MJi dG JaJYdgG (B/s - (3aQjH, HGJQjTjGs ((3GdQjGV (B:s (3ecJHI LQjQ,s, 2006)
(3jJfGhd GdcJGH cjajI GdJYGed eY GdehXajjf hYed YdGbGJ dHjY CaVd hJMbjb GdGLJeGYjI(B.s
Keywords: (3GdfLGM GdEOGQjs